Pengaruh Model Pembelajaran Numbered Head Together (NHT) Dan Teams Games Tournament (TGT) Terhadap Hasil Belajar Matematika Ditinjau Dari Gaya Belajar Siswa Kelas Vii Semester Genap Mts Negeri Surakarta 1 Tahun 2015/2016 - EFENDI, Oky Ardian, Drs. Slamet HW, M.Pd (2016)
The purpose of research is to determine the effect of NHT and TGT learning model on the learning outcomes of mathematics, the influence of learning styles on mathematics learning outcomes, interaction between the learning models and learning styles on mathematics learning outcomes. This type of research is quantitative with quasiexperimental research design. The population of this study were all students of class VII MTs Negeri Surakarta 1 second semester of the 2015/2016 academic year. The research sample consisted of two classes. The sampling technique using cluster random sampling. Data collection methods to test and documentation. Data were analyzed using two-way analysis of variance with different cell. The results of data analysis using a significance level of 5% was obtained: (1) There is effect of model NHT and TGT for mathmatics learning outcome, with FA = 22,27 (2) there is effect of learning style for mathematics learning outcome, with FB = 8,40 (3) there is no intraction between learning models and learning style for mathmatics learning outcome, with FAB = 0,029.